1986
DOI: 10.1104/pp.81.4.1140
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Activity of Catalase (EC 1.11.1.6) in Relation to the Dormancy of Grapevine (Vitis vinifera L.) Buds

Abstract: Catalase activity in grapevine (Vitis vinifera L.) buds cv. ;Perlette.' increased to a maximum in October and thereafter decreased within 3 months to less than half its maximal rate. The decrease in catalase activity coincided with the decline in temperature during winter. The rate of sprouting of buds forced at 23 degrees C was negatively related to the activity of catalase. Artificial chilling of grapevine canes at 5 degrees C resulted in a 25% decrease of catalase activity in the buds after 3 days and 31% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0
3

Year Published

1991
1991
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 17 publications
4
41
0
3
Order By: Relevance
“…In group RD, sequences related to metabolism and oxidation-reduction were the most abundant, which fits well with the idea that some basic metabolic activation is required to restart growth and cell division following dormancy and with S1 S2 S3 S4 S5 Z1 Z2 Z3 Z4 S1 S2 S3 S4 S5 Z1 Z2 Z3 S1 S2 S3 S4 S5 Z1 Z2 Z3 Z4 S1 S2 S3 S4 S5 Z1 Z2 Z3 those previous works linking oxidative stress and dormancy release (Nir et al, 1986;Scalabrelli et al, 1991;Or et al, 2002). On the other side, group DR was rich in stress and defence genes, as dormant tissues must be prepared against drought and cold stresses appearing during winter time.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In group RD, sequences related to metabolism and oxidation-reduction were the most abundant, which fits well with the idea that some basic metabolic activation is required to restart growth and cell division following dormancy and with S1 S2 S3 S4 S5 Z1 Z2 Z3 Z4 S1 S2 S3 S4 S5 Z1 Z2 Z3 S1 S2 S3 S4 S5 Z1 Z2 Z3 Z4 S1 S2 S3 S4 S5 Z1 Z2 Z3 those previous works linking oxidative stress and dormancy release (Nir et al, 1986;Scalabrelli et al, 1991;Or et al, 2002). On the other side, group DR was rich in stress and defence genes, as dormant tissues must be prepared against drought and cold stresses appearing during winter time.…”
Section: Discussionsupporting
confidence: 50%
“…Previously, other peroxidases have been related to the fulfillment of the chilling requirement in Vitis riparia buds (Mathiason et al, 2009) and to dormancy release in buds of leafy spurge (Jia et al, 2006). Earlier studies suggest a role of hydrogen peroxide (H 2 O 2 ) in budbreak regulation, based on catalase activity inhibition and H 2 O 2 accumulation occurring during the natural or hydrogen cyanamide induced breaking of bud dormancy in grapevine (Nir et al, 1986;Pérez et al, 2008). This points to a putative detoxifying role of peroxidases by degrading H 2 O 2 produced during budbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Activity of CAT is altered due to metabolic changes during various growth stages. In addition many environmental factors such as light (Feierabend et al, 1992) temperature (Omran, 1980;Nir et al, 1986), O 2 and CO 2 concentration (Fair et al, 1973;Monk et al, 1987) have been shown to influence catalase activity in mature plants. In fact this high level of CAT activity induced by grains drying was associated with a decrease in hydrogen peroxide level and in lipid peroxidation studied by Bailly et al (2004).…”
Section: Discussionmentioning
confidence: 99%
“…In such areas, the chilling requirement for budbreak are not fulfilled, leading to a late leafing, reduced and no regular sprouting and, consequently, decrease in yield, causing significant economic loses. Chilling exposing necessary for normal bud growth ranges between 50 and 400h at temperatures of 7.0 o C, varying for each grapevine cultivar and 'Niagara Rosada' grapevines needs about 100 h (DOKOOZLIAN et al, 1998), Previous literature indicates that the exposition of the buds to chilling inhibits the activity of the catalase, enzyme present in aerobics cells that decomposes the hydrogen peroxide (H2O2) in molecular oxygen and H2O (NIR et al, 1986). Its physiologic function eliminates the excess of H2O2 produced during the cellular metabolism, avoiding its accumulation and consequent cellular damage.…”
Section: Introductionmentioning
confidence: 99%
“…After that, the plant leads to H2O2 deintoxication through a sequence of reactions connected to the pentose phosphate pathway, leading to an increase of reduced nucleotides NAD(P)H, raising the metabolism and the induction of dormancy termination, bud burst and rapid growth (NIR et al, 1986). According to PINTO et al (2007), these metabolic changes has as consequence the increase on the levels of AMP/ATP intracellular relation that induces proteinkinases SNF, that plays a role in the transduction signal system for endodormancy end of buds.…”
Section: Introductionmentioning
confidence: 99%